2016
DOI: 10.1007/s00360-016-1041-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thermal traits of Polistes dominula and Polistes gallicus, two European paper wasps with strongly differing distribution ranges

Abstract: The two paper wasps, Polistes dominula and Polistes gallicus, are related species with strongly differing distribution ranges. We investigated thermal tolerance traits (critical thermal limits and metabolic response to temperature) to gain knowledge about physiological adaptations to their local climate conditions and to get evidence for the reasons of P. dominula’s successful dispersion. Body and ambient temperature measurements at the nests revealed behavioural adaptations to microclimate. The species differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 62 publications
(96 reference statements)
0
19
1
Order By: Relevance
“…In contrast to the SMR, the upper thermal limit or CT max of activity we determined for Polistes biglumis (CT max = 47.2 • C) was virtually identical to that of Polistes dominula (CT max = 47.1 • C) [18]. This is a surprising result, as one would expect that the species living in a warmer habitat has been endowed with a higher thermal tolerance (upper thermal limit), as was determined in seed bug species [39].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In contrast to the SMR, the upper thermal limit or CT max of activity we determined for Polistes biglumis (CT max = 47.2 • C) was virtually identical to that of Polistes dominula (CT max = 47.1 • C) [18]. This is a surprising result, as one would expect that the species living in a warmer habitat has been endowed with a higher thermal tolerance (upper thermal limit), as was determined in seed bug species [39].…”
Section: Discussioncontrasting
confidence: 64%
“…The point of time when controlled motoric activity ceased and muscle spasms started was determined via behavioral observation, and the Insects 2020, 11, 165 5 of 12 temperature at that time (CT max ) was extracted from the logger file of a thermocouple, which was recording the temperature inside the measurement chamber. For further information see [13,18].…”
Section: Critical Thermal Maximum (Ct Max )mentioning
confidence: 99%
“…In honeybee ( Apis mellifera ) populations adapted to colder climates, major energy‐producing mitochondrial pathways were found to be upregulated (Parker et al ., 2010). In both ants ( Aphaenogaster iberica ; Shik et al ., 2019) and wasps ( Polistes dominula , Kovac et al ., 2017), workers from populations found at higher altitudes had higher metabolic rates than did workers from populations found at lower altitudes.…”
Section: Physiological and Molecular Adaptationsmentioning
confidence: 93%
“…Indeed, social insect species living in more mesic habitats further north were found to have a lower CT max than those living in more xeric habitats further south [ants (Marsh, 1985; Morton & Christian, 1994; Oberg, del Toro, & Pelini, 2012); bees (Ruttner, 1988; Abou‐Shaara, 2015); termites (Janowiecki et al ., 2019)]. Northern European species of Polistes wasps were found to have a lower CT min than species from the Mediterranean (Kovac et al ., 2017). Ants display within‐species variation in thermal tolerance: populations from higher latitudes were shown to have a lower CT min than populations from lower latitudes ( Leptothorax acervorum ; Heinze et al ., 1998).…”
Section: Thermal Tolerance and Environmental Conditionsmentioning
confidence: 99%
“…In general, in evolutionary adaptation processes species have developed special physiological features to cope with the environmental conditions of their habitat. In Polistes dominula and Polistes gallicus, it could be shown that these species have developed thermal traits according their thermal environment [10]. The aim of this study was to investigate the thermoregulatory behavior of these two closely related species in different habitats with differing climate, under special consideration of the microclimate conditions.…”
Section: Introductionmentioning
confidence: 99%